Determining the influence of parameters for gas-air flows on the thermal process of producing iron ore pellets - Lobov, Vyacheslav; Lobova, Karina; Mytrofanov, Oleksandr (Eastern-European Journal of Enterprise Technologies, 2019)
We present the results of the study on changes in temperature of gas-air flows at the outlets from calcination zones and recuperation zones of a conveyor-calcination plant. We determined the influence of these temperatures on other technological zones. We showed that that the average volume temperatures of gas-air flows from calcination and recuperation zones are the exponential dependences on temperatures of gas-air flows above a layer of pellets in these zones. It was established that an increase in the speed of movement of calcination carts from 0.011 m/s to 0.06 m/s leads to a decrease in the average volume temperature of a heated gas-air flow by 1.7 times. An increase in the height of a pellet layer on calcination carts by 30 percent with constant gas permeability of this layer leads to an exponential decrease in the average volume temperature of a gas-air flow by 2.5 times at the outlet from the calcination and recuperation zones. The average volume temperatures of gas-air flows decrease at the outlet of a pellets layer up to three times at a change in the pressure by 20 % in the calcination zone and at the constant movement speed of calcination carts of 0.049 m/s, the height of a pellets layer of 450 mm and the porosity of a pellets layer of 0.45 m³/m. We used a mathematical model to analyze a temperature mode of a gas-air flow at the outlet of the pellet calcination zone. The basis of the mathematical model was the relation between the inlets and outlets of technological zones of the plant by equations of gas dynamics and heat exchange and mass transfer. The study made it possible to develop and present an automated control system for a smoke exhauster for average volume temperatures of gas-air flows at the outlet from the technological zones of calcination and recuperation of the plant. It is possible to use it under industrial conditions. It improves thermal and gas-dynamic operation of technological zones of a conveyor calcination plant